PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA PROFESI (UTP) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SDN KINGKING 2 TUBAN: PENGEMBANGAN MEDIA PEMBELAJARAN - Iis Daniati Fatimah; nOVIALITA ANGGA WIRATAMA (Jurnal Tunas Pendidikan, 2024)
This development research aims to determine the validity, practicality and effectiveness of learning media. The research method used is development research or R&D (research and development) with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, Evaluate. The test subjects in the research were fourth grade students at SDN Kingking 2 Tuban. Data collection was carried out using interview techniques, observation, questionnaires, tests and documentation. Data instruments were obtained from expert validation sheets, teacher and student response questionnaires and test sheets. The research results regarding the validity of UTP media were declared very valid and obtained a percentage of media experts of 89,4%, material experts 100%. The results of the teacher response questionnaire were stated to be very practical with a percentage of 93.33%. The learning outcomes test obtained 89,28% with high criteria. Based on the data obtained, the UTP (professional snakes and ladders) learning media was declared valid, practical and effective for use in the learning process.